Indian Council of Medical Research consensus document for the management of gastric cancer - Shrikhande, Shailesh V. (Indian J Med Paediatr Oncol, 2014)
The document is based on consensus among the experts and best available evidence pertaining to Indian population and is meant for practice in India. Evaluation of a patient with newly diagnosed gastric cancer should include essential tests: A standard white light endoscopy with multiple biopsies from the tumor for confirmation of the diagnosis, a computed tomography (CT) scan (multi-detector or helical) of the abdomen and pelvis for staging with a CT chest or chest X-ray, and complete blood counts, renal and liver function tests. Endoscopic ultrasonography/ magnetic resonance imaging/positron emission tomography-CT is not recommended for all patients. For early stage disease (IA/B, N0), surgery alone is recommended. The need for adjuvant treatment would be guided by the histopathological analysis of the resected specimen. For locally advanced stage (IB, N(+) to IIIC), neoadjuvant chemotherapy may be considered to downstage the disease followed by surgery. This may be followed by adjuvant chemotherapy (as part of the peri-operative chemotherapy regimen). Patients with stage IV/metastatic disease must be assessed for chemotherapy versus best supportive care on an individual basis. Clinical examination including history and physical examination are recommended at each follow-up visit, with a yearly CT scan of the chest, abdomen, and pelvis. HER2 testing should be considered in patients with metastatic disease. 5-FU may be replaced with capecitabine if patients do not have gastric outlet obstruction. Cisplatin may be replaced with oxaliplatin in the regimens.